A Study On Women Drug Dependents And Carers Of Drug Dependents In Malaysia. - Navaratnam, V.; Foong Kin, Foong Kin; Samuel, Rachel (Pusat Penyelidikan Dadah Kebangsaan, Universiti Sains Malaysia, 1992)
In most countries of the world, substance misuse has ceased to be seen as a problem affecting a few unfortunate individuals or a miscreant sub-group. The perception now is• of a growing international problem which incurs heavy costs for society and the community as well as for individuals personally involved